2016
DOI: 10.11646/zootaxa.4073.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A new genus and twenty new species of Australian jumping plant-lice (Psylloidea: Triozidae) from Eremophila and Myoporum (Scrophulariaceae: Myoporeae)

Abstract: The Triozidae is a diverse, cosmopolitan family of jumping plant-lice (Hemiptera: Psylloidea) from an exceptionally diverse range of plant families, but with few described Australian species. As a direct outcome of the Australian Biological Resources Study Bush Blitz species discovery program, many new Psylloidea from novel host plants in remote localities have been revealed. In this study a new genus Myotrioza Taylor gen. nov. and 20 new species are described from southern and central Australia which also est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Despite distinct regional structure in the genetic variation of Trioza urticae , overall genetic divergence, particularly considering the extremely large geographic range, is relatively small (<3%) and is well within intraspecific divergence reported for other psyllid taxa [Percy 2003, Taylor et al 2016]. We therefore consider the observed variation in Trioza urticae to be typical and not suggestive of reproductive isolation indicative of incipient species divergence.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Despite distinct regional structure in the genetic variation of Trioza urticae , overall genetic divergence, particularly considering the extremely large geographic range, is relatively small (<3%) and is well within intraspecific divergence reported for other psyllid taxa [Percy 2003, Taylor et al 2016]. We therefore consider the observed variation in Trioza urticae to be typical and not suggestive of reproductive isolation indicative of incipient species divergence.…”
Section: Discussionsupporting
confidence: 48%
“…One study, using the small tortoiseshell butterfly ( Aglais urticae L.), found high levels of gene flow and little or no population or geographic structure across the Palaearctic [Vandewoestijne et al 2004], which the authors attributed to rapid population expansion facilitated by the ubiquitous and widespread distribution of the host. The relatively typical overall genetic divergence in Trioza urticae compared to other psyllid systems [Percy 2003, Taylor et al 2016] suggests that range expansions are also facilitated by the abundant frequency and breadth of host distribution, but these are apparently more limited and less rapid than in the small tortoiseshell butterfly. Although the host plants were also sampled during collection of the nettle psyllids for this study, the observed morphological and cytological diversity in the nettle samples is complex [Cronk et al 2016] and there are no obvious or clear associative patterns with the structure of variation in the nettle psyllid.…”
Section: Discussionmentioning
confidence: 99%
“…Percy (2003) found that intra-specific mitochondrial divergence varied between 1 and 10% for psyllid species collected on different islands, but was restricted to an upper limit of 3% for continental species. Taylor et al (2016) identified a 5-6% divergence as the threshold that best matched morphological and ecological The lower level corresponds to the tree species the insects were collected from. The second level corresponds to the Mycopsylla spp.…”
Section: Discussionmentioning
confidence: 99%
“…Of the Psylloidea, the family Triozidae feed on by far the greatest number of plant families (see Hollis, 1984;Ouvrard et al, 2015;Ouvrard, 2019), although certain composite lineages within often show radiations on discrete plant genera and plant families, e.g., Casuarinicola on Casuarina (Taylor et al, 2010), Acanthocasuarina on Allocasuarina (Casuarinaceae) (Taylor et al, 2011), Myotrioza on Eremophila and Myoporum (Scrophulariaceae) (Taylor et al, 2016) and Pariaconus on Metrosideros (Myrtaceae) (Percy, 2017). Based on the land mass, the Australian triozid fauna is considered depauperate, with 59 described species in seven genera from nine plant families of which the genus Trioza comprises just 10 species (Taylor et al, 2016). Contrastingly, the New Zealand triozid fauna comprises 60 species in five putative genera (i.e., two undescribed) from at least 15 plant families of which the genus Trioza comprises 56 putative species (of these 23 taxa are undescribed) (Martoni et al, 2016(Martoni et al, , 2018).…”
Section: Introductionmentioning
confidence: 99%